RESULTS OF APPLYING COMPLEX THERAPEUTIC METHODS IN DIFFERENTIATED THYROID CANCER (Western European Journal of Medicine and Medical Science, 2025)
This research focuses on analyzing the effectiveness of combined treatment for differentiated thyroid cancer (DTC), taking into account both morphological features and the molecular-genetic profile of the tumor. Between 2014 and 2024, 300 patients with confirmed DTC were examined at the branch of Tashkent city of the Republican Specialized ScientificPractical Medical Center of Oncology and Radiology. A comparative study was conducted between an improved diagnostic-therapeutic algorithm—including ultrasound, fine-needle aspiration biopsy, molecular testing, and individualized surgical and targeted therapy—and the conventional approach. Findings demonstrated that the improved algorithm provided higher two-year disease-free survival (78.1% versus 66.5%; p=0.033). Adverse prognostic indicators were associated with TERT, RAS, PAX8-PPAR-γ, and BRAF-V600E mutations, particularly their combinations (e.g., RAS+PAX8-PPAR-γ, HR=4.271; p=0.005). Extended thyroidectomy with lymph node dissection improved locoregional control and reduced recurrence risk. In conclusion, the integration of molecular profiling and personalized surgical strategy into standard DTC management enhances survival, reduces recurrence rates, and proves economically beneficial, reducing treatment costs by an average of 3.8 million UZS per patient.